2017
DOI: 10.1161/atvbaha.117.309212
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular Cyclophilin A, Especially Acetylated, Causes Pulmonary Hypertension by Stimulating Endothelial Apoptosis, Redox Stress, and Inflammation

Abstract: Objective Oxidative stress and inflammation play key roles in development of pulmonary arterial hypertension (PAH). Cyclophilin A (CypA) is secreted in response to oxidative stress, and promotes inflammation and cardiovascular disease. Endothelial cell (EC) dysfunction is an early event in the pathogenesis of PAH. We evaluated the role of extracellular CypA in PAH, and compared the effects of acetylated CypA (AcK-CypA, increased by oxidative stress) and CypA on EC dysfunction. Approach and Results In transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…Our results showed significant upregulation of CLDN1 (Figure f,g; p < 0.01) in PAH models. Moreover, cell inflammatory signals like IkBα have been used to access cell dysfunction in PAH model in Xue, Sowden, and Berk () research too. We measured the protein expression of IkBα and p‐IkBα.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed significant upregulation of CLDN1 (Figure f,g; p < 0.01) in PAH models. Moreover, cell inflammatory signals like IkBα have been used to access cell dysfunction in PAH model in Xue, Sowden, and Berk () research too. We measured the protein expression of IkBα and p‐IkBα.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, several experiments have been conducted. Xue et al 63 demonstrated that endothelium-specific overexpression of cyclophilin A, which has been shown to induce vascular injury through multiple mechanisms, including endothelial dysfunction and vascular smooth muscle proliferation, caused spontaneous PAH in mice in vivo. Mechanistically, extracellular cyclophilin A induced endothelial cell dysfunction via endothelial apoptosis, inflammation, and oxidative stress production.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Mechanistically, extracellular cyclophilin A induced endothelial cell dysfunction via endothelial apoptosis, inflammation, and oxidative stress production. 63 Meloche et al 64 proposed a mechanism by which coronary artery disease develops in PAH patients; expression of bromodomaincontaining protein 4, which promotes atherogenic processes through inflammatory responses in endothelial cells, was increased not only in the lungs of PAH patients but also in their coronary arteries, promoting vascular remodeling through enhanced proliferation and suppressed apoptosis in vascular smooth muscle cells. These findings provide a clue for understanding why PAH patients are likely to be complicated by coronary artery disease even in the absence of metabolic disorders.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…In addition, CyPA and Bsg were also up-regulated in the lung from cROCK1 −/− mice after pressure overload, in which vascular remodeling and postcapillary PH were significantly developed. Both CyPA and Bsg are known to accelerate PH by stimulating oxidative stress and inflammation (33,48). Similarly, CyPA and Bsg in the lung may also contribute to the development of postcapillary PH, which is primarily caused by the passive backward transmission of elevated filling pressure induced by LV dysfunction.…”
Section: Different Roles Of Rock1 and Rock2 In Ros Production Inmentioning
confidence: 99%
“…Celastrol suppresses the activity of NF-κB, which up-regulates inflammatory genes and enhances cardiac hypertrophy (52) and pulmonary vascular remodeling (53). As CyPA and Bsg activate NF-κB (48,54), the effect of celastrol on HF may have been due to the inhibition of CyPA/Bsg-NF-κB axis, which enhances ROS generation and inflammatory status. However, the beneficial effects of celastrol may involve mechanisms other than reducing CyPA and Bsg.…”
Section: Celastrol As a Novel Therapeutic Agent For Hf Patients With mentioning
confidence: 99%